Load envelope concept of offshore wind turbine monopile with the allowed inclined angle in sand - Zhang, Zhongchang; Zhang, Yaru; Xu, Mengtao; Zha, Xing; Rui, Shengjie (Marine georesources & geotechnology, 2024)
Monopiles are the economic choices in shallow water as the foundations of offshore wind turbines (OWTs). Maximum allowed rotation θ = 0.25° is set as the criterion in the serviceability limit state design. However, the allowed load combinations of monopiles in sand are not fully revealed and understood satisfying the criterion. In this paper, load envelop concept to ensure the allowed monopile rotation less than 0.25° was proposed to understand all possible load combinations on monopiles for the OWTs. Finite element models based on the sand hypoplastic model with inter-granular strain were established. After verification with the centrifuge results, different load-displacement curves were acquired by changing loading paths to acquire the envelope surfaces meeting the criterion. Finally, the most likely load combinations of the OWTs were particularly analysed. Under the condition with θ = 0.25°, the allowed horizontal loads and the bending moments are closely coupled. The calculated envelop curves composed of maximum allowed loads can be well fitted and described by the cubic function. This note provides a method to obtain load combinations with allowed inclinations, which is beneficial to understand the load states of monopile for OWTs.